Classification of Chemical Residues in laboratories of the Universidad Nacional - Mora, José Carlos (2011)
During the years 2008-2010, inventories were carried out regarding chemical wastes manipulated in the Universidad National. In order to gather such information for these inventories, laboratories’ directors filled out a form. Using the preliminary given information, wastes were classified into nine classes, allowing this the identification of distribution patterns, as well as the identification of higher and lower hazardous wastes stored and handled. Analytical procedures and chemical reagents that contribute to those hazardous classes waste detected. As a conclusion, in order to conduct an adequate and safe working environment, it is necessary to develop chemical waste databases. Waste classification is the first step to create a framework to develop and apply the right actions related with waste management aspects, economic support, regulation requirements, safety and technical investment to look forward to protect worker health and the environment around.